Layer-by-layer assembly of insulin on nano-liposome for loading enhancement - Ho, Wan Ying (2018)
The onset and development of oral drug delivery systems have promised an advantageous key for obstacles present in the current treatment of diabetes mellitus. With the advancements of liposomal nano-carriers, oral delivery of insulin is dynamically moving towards its feasibility in the near future. Despite the numerous researches and studies, the efficacy of liposomal oral delivery of insulin is afflicted with unflagging barriers such as poor bioavailability and low insulin loading. As such, this study resolves to address these challenges through layer-by-layer deposition of nano-liposomes. Multi-layers were developed by alternating the assembly of oppositely-charged polyelectrolytes via electrostatic attractive forces. The desired particle sizes and surface charges were achieved through optimization of chitosan and insulin layers, followed by characterisation of the particle sizes, PDI and zeta potential of alternated layers executed by DLS measurements with the use of the Zetasizer Nano. Relatively small average particle sizes, low PDI values and charge reversals were obtained for all layers, thereby proceeding with stability tests over a duration of four weeks to investigate the behaviour of each layer in both PBS and SGF solutions. Particles were proven to be relatively stable in PBS of pH 7.4 in comparison with SGF of pH 1.1-1.3 with sodium chloride (NaCl) as one of its compositions, mainly due to the presence of salt which weakened the electrostatic repulsion among nanoparticles as ionic strength increased. The results presented a significant improvement in insulin loading when in-vitro release studies were carried out, which appeared to be a pulsatile release drug delivery system. With the aforementioned, this research looks into the potential of the layer-by-layer assembly of nano-liposomes as a promising oral insulin delivery technique for diabetes management.